Introduction - Jo Mynard (Studies in Self-Access Learning Journal)
Welcome to the Final issue of SiSAL journal for 2023. It was our pleasure to work with authors from diverse countries. This issue contains three papers in the main section, one paper in the Ethnographies of Self-Access section, and three reviews (edited by Hisako Yamashita). Contributors are based in India, Indonesia, Oman, the Philippines, and Thailand.